2016
DOI: 10.4306/pi.2016.13.5.566
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Personality, Sense of Efficacy, and Stress in Korean Teachers

Abstract: Several studies have linked teachers' personality characteristics and sense of efficacy to stress. However, investigating the relationship between these three constructs in this context was limited. This study aims to investigate the relationship between personality, sense of efficacy and perceived stress among Korean teachers. A total of 137 teachers working in elementary, middle, and high schools located in Seoul, South Korea were recruited for the study. The participants were administered Temperament and Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
0
9
0
2
Order By: Relevance
“…It is a common observation that people are clearly diverse in their psychological and physiological responses to stressors and challenging environments [3,4]. Personality may be an important factor explaining this diversity, as it can have an effect on a person’s assessment and perception of a potentially stressful situation and a subsequent potentially diverse biological reaction [5,6]. Personality provides an important biological trait, because of its hereditary bases, as well as linkage with intraindividual compatibility [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a common observation that people are clearly diverse in their psychological and physiological responses to stressors and challenging environments [3,4]. Personality may be an important factor explaining this diversity, as it can have an effect on a person’s assessment and perception of a potentially stressful situation and a subsequent potentially diverse biological reaction [5,6]. Personality provides an important biological trait, because of its hereditary bases, as well as linkage with intraindividual compatibility [7].…”
Section: Introductionmentioning
confidence: 99%
“…Trait-based perspectives such as the 16-factor theory of Cattell, the three-factor model of the Eysencks, and, finally, the five-factor approach of personality have made remarkable progress in theories and methods of personality assessment [59]. The two personality theories are including one the five-factor model of personality that uses the NEO-Personality Inventory (NEO-PI) as a measurement instrument [60], and the other psychobiological theory of personality, which uses the Eysenck Personality Questionnaire and Temperament and Character Inventory as measurement instruments [6,61,62]. Among objective personality tests, the dimensions of the big five personality (for example, neuroticism, extraversion, openness to experience, agreeableness, and conscientiousness) have received more attention than other personality constructs [63].…”
Section: Introductionmentioning
confidence: 99%
“…Self-efficacy among teachers has been shown to be related to their performance in relation to the teaching-learning process, as well as their emotional aspects, regarding emotional exhaustion and satisfaction towards work (Mahler, Großschedl, & Harms, 2017). A study with Korean teachers demonstrated that the sense of efficacy positively correlates with persistence, self-directedness, cooperativeness, and self-transcendence, acting as a protective resource against stress (Park et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The parameters used to evaluate the working environment include interpersonal conflicts, complaints, overtime, letters of recall, absenteeism and accidents at work. They can all be considered indicators of the possible development of work-related stress [34][35][36][37], as well as a manifestation of organizational malaise [55,56].…”
Section: Introductionmentioning
confidence: 99%
“…Psychosocial risk is discussed as the result of the interaction between the work context and the subjective characteristics of the worker [63]. Others, however, have analysed the relationship between stress and personality traits [56,64,65].…”
Section: Introductionmentioning
confidence: 99%